2010
DOI: 10.1055/s-0029-1240940
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Artemisinin Content through Four Cycles of Recurrent Selection with Relation to Heritability, Correlation and Molecular Marker inArtemisia annuaL.

Abstract: Due to the high demand and low yield of the anti-malarial drug artemisinin in natural populations of Artemisia annua (Quinghao), an attempt has been made to enhance the artemisinin content through 4 cycles of recurrent selection (C(0)-C(3)) using selected genotypic and phenotypic traits. Based on their phenotypic and genotypic characteristics, the top 5% plants of each cycle were selected, and their seedlings were planted in poly-cross block to produce seeds for the subsequent generation. A significant increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Similar results were obtained by Jain et al (1996), who concluded that the synthesis and the accumulation of artemisinin are independent from the effect of metric traits such as plant height, stem diameter and dry matter production. In contrast, Paul et al (2010) observed a positive correlation of artemisinin content with plant height and branch intensity, and Liao et al (2009) suggested that taller plants with thick stalks and a moderate number of branches should be selected for the generation of a new A. annua variety with a high artemisinin content and yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were obtained by Jain et al (1996), who concluded that the synthesis and the accumulation of artemisinin are independent from the effect of metric traits such as plant height, stem diameter and dry matter production. In contrast, Paul et al (2010) observed a positive correlation of artemisinin content with plant height and branch intensity, and Liao et al (2009) suggested that taller plants with thick stalks and a moderate number of branches should be selected for the generation of a new A. annua variety with a high artemisinin content and yield.…”
Section: Resultsmentioning
confidence: 99%
“…The correlated traits can assist in the selection process and decrease costs because of the straightforwardness of selecting traits that enable more practical measurements, which can result in greater genetic progress. A positive correlation between the biomass production and the artemisinin yield was found by Magalhães (1996) and Marchese (2006); moreover, the artemisinin content exhibited a direct correlation with plant height and branching intensity (Liao et al, 2009, Paul et al, 2010 and a high correlation (0.987) with trichome density (Zhang et al 2006). Regarding the essential oil yield, Marchese and Figueira (2005) reported that this trait can be correlated with photosynthesis because increased oil production is typically associated with higher radiation and a higher photosynthetic rate in plants.…”
Section: Introductionmentioning
confidence: 89%
“…The high expected genetic advance for branching pattern and leaf characters signifies that considerable improvement could be achieved in these traits by selection from segregating populations. The high heritability and high expected genetic gain coupled with moderate GCV exhibited by plant height, branching pattern, leaf morphology (Paul et al 2010) and artemisinin in the IInd and IIIrd T imply that these are under additive gene effects and could be relied upon for further selection based on phenotypic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Artemisia annua is an annual and short day plant. Most of the Indian high-yielding varieties, such as Jeewanraksha and Suraksha (1-1.2 %; Kumar et al 1999) and CIM Arogya (1-1.16 % with high herbs; Khanuja et al 2008;Paul et al 2010Paul et al , 2014, are late-flowering varieties, matures after attaining full vegetative growth. The artemisinin yield is expected to depend on the inheritance, pattern of crossing and climatic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This necessitates searching for novel structural and regulatory genes involved in artemisinin biosynthesis in the plant. Based on this, ‘CIM-Arogya’, a SCAR-marked high yielding (∼1.2% artemisinin content on dry weight basis) variety of A. annua [5], [14], [15], similar in artemisinin content to the European variety ‘Artemis’, was analyzed in the present study. This variety is well accepted by the industry and grown extensively by farmers.…”
Section: Introductionmentioning
confidence: 99%